Proteinuria as the cause of early dose modification in Japanese patients with metastatic colorectal cancer treated with fruquintinib: a multicenter real-world study - Shohei Udagawa; Chihiro Ishizuka; Hiroki Osumi; Toshiharu Hirose; Natsuko Okita; Hidekazu Hirano; Hirokazu Shoji; Ken Kato; Koichiro Yoshino; Keitaro Shimozaki; Shota Fukuoka; Takeru Wakatsuki; et al. (International Journal of Clinical Oncology, 2026)
Abstract Background Fruquintinib has demonstrated survival benefits in patients with previously treated metastatic colorectal cancer (mCRC) in phase III trials. However, real-world data in Japanese patients remain limited. This study evaluated the effectiveness and safety of fruquintinib in routine clinical practice. Methods We conducted a retrospective observational study at two cancer centers. Patients treated with fruquintinib for mCRC between November 2024 and December 2025 were included. Clinical outcomes and safety were evaluated, and exploratory analyses were performed according to starting dose, relative dose intensity (RDI), and selected adverse events (AEs). Results A total of 92 patients were included. Fruquintinib was initiated at 5 mg in 72 patients (78.3%) and at 4 mg in 19 patients (20.7%). The disease control rate was 37.4%, and no objective responses were observed. Median time to treatment failure was 2.57 months (95% confidence interval [CI], 2.23–3.33), and median overall survival was 8.83 months (95% CI, 7.46–not estimable). The median follow-up period was 5.48 months. Grade ≥ 3 AEs occurred in 39 patients (42.4%), and treatment discontinuation due to AEs occurred in 4 patients (4.3%). Proteinuria was the leading cause of early dose reduction, with 39.1% of dose modifications occurring within 28 days. In exploratory analyses, no clear differences in outcomes were observed according to starting dose, RDI, hypertension, or proteinuria. Conclusions Fruquintinib demonstrated feasible effectiveness and manageable toxicity in Japanese patients with mCRC. Proteinuria was a major determinant of treatment feasibility and frequently led to early dose modification.